Who stole my customer?? : winning strategies for creating and sustaining customer loyalty - Thompson, Harvey (Pearson Prentice Hall, 2004)
Current customers are up to nine times as profitable as new ones, but keeping customers has never been tougher. It's time you developed a customer-defined, outside-in vision of your business, plus the capabilities and infrastructure to make it real. Thompson led customer-focused process improvement at Lou Gerstner's IBM, helping to drive one of the greatest transformations in business history. Drawing on his experiences with IBM and other world-class enterprises, he'll help you discover how your customers have changed, what they're expecting now, which facets of customer satisfaction actually drive loyalty ... and where you're most vulnerable. Next, Thompson will show how to engineer a winning customer experience around your customer's view of the world, and how to "institutionalize" loyalty, making it resilient enough to resist virtually any competitor